Novel p53 therapies for head and neck cancer - Mario R. Castellanos; Quintin Pan (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2016)
Inactivation of the tumor suppressor p53 is the predominant pathogenetic event in head and neck squamous cell carcinoma (HNSCC). The p53 pathway in HNSCC can be compromised through multiple mechanisms including gene mutations, hyperactivation of endogenous negative p53 regulators and by the human papillomavirus E6 protein. Inactivation of p53 is associated with poor clinical response and outcome; therefore, restoration of the p53 signaling cascade may be an effective approach to ablate HNSCC cells. Viral approaches to restore p53 activity in HNSCC have been well-studied and shown modest activity in clinical trials. Recent work has focused on high-throughput screens and rational designs to identify and develop small molecules to rescue p53 function. Several p53-targeting small molecules have demonstrated very promising activity in pre-clinical studies but have yet progressed to the clinical setting. Further development of p53 therapies, in particular chemical approaches, should be prioritized and evaluated in the HNSCC setting. Keywords: Head and neck cancer, Tumor suppressor p53, Gene therapy, Human papillomavirus, p53 mutations